Characterization of CaO-CuO-CeO2 mixed oxide synthesized by the impregnation and investigation of its reusability - Hue, Hoang Thi Huong; Quang, Nguyen Van; Anh, Nguyen Thi (Vietnam Journal of Science and Technology, 2017)
CaO-CuO-CeO2 mixed oxide was prepared by the impregnation method and used as the catalyst for the complete decomposition of phenol in the presence of hydrogen peroxide. The CaO-CuO-CeO2 mixed oxide were characterized by XRD, SEM, BET, H2-TPR and Raman spectroscopy. The results indicated that there were three CuO species in the mixed oxide: the finely dispersed CuO species on the surface of CeO2, the Ce1-x-yCuxCayO2-d solid solution and the bulk CuO. Most of particles have clear morphology with relatively uniform size in the range of 30 - 50 nm and the BET surface area was 37.96 m2/g. After three times of use, the catalytic activity of CaO-CuO-CeO2 mixed oxide was still relatively high and much higher than the mixed oxide CaO-CeO2 and CuO-CeO2.